Development of an environmental contextual factor item set relevant to global functioning and health in patients with axial spondyloarthritis. (17th September 2021) - Kiltz, Uta; Boonen, Annelies; van der Heijde, Désirée; Bautista-Molano, Wilson; Burgos Vargas, Ruben; Chiowchanwisawakit, Praveena; El-Zorkany, Bassel; Gaydukova, Inna; Geher, Pal; Gossec, Laure; Gilio, Michele; Grazio, Simeon; et al.
Abstract: Objective: To describe the development of an Environmental contextual factors (EF) Item Set (EFIS) accompanying the disease specific Assessment of SpondyloArthritis international Society Health Index (ASAS HI). Method: First, a candidate item pool was developed by linking items from existing questionnaires to 13 EF previously selected for the International Classification of Functioning, Disability and Health (ICF) /ASAS Core Set. Second, using data from two international surveys, which contained the EF item pool as well as the items from the ASAS HI, the number of EF items was reduced based on the correlation between the item and the ASAS HI sum score combined with expert opinion. Third, the final English EFIS was translated into 15 languages and cross-culturally validated. Results: The initial item pool contained 53 EF addressing four ICF EF chapters: products and technology (e1), support and relationship (e3), attitudes (e4) and health services (e5). Based on 1754 responses of axial spondyloarthritis patients in an international survey, 44 of 53 initial items were removed based on low correlations to the ASAS HI or redundancy combined with expert opinion. Nine items of the initial item pool (range correlation 0.21–0.49) form the final EFIS. The EFIS was translated into 15 languages and field tested in 24 countries. Conclusions: An EFIS is available complementing the ASAS HI and helps to interpret the ASAS HI results by gaining an understanding of the interaction between a health condition and contextual factors. The EFIS emphasizes the importance of support and relationships, as well as attitudes of the patient and health services in relation to self-reported health.